Traumatic brain injury in pedestrian–vehicle collisions: Convexity and suitability of some functionals used as injury metrics. (November 2016) - Sánchez-Molina, D.; Arregui-Dalmases, C.; Velázquez-Ameijide, J.; Angelini, M.; Kerrigan, J.; Crandall, J.
Highlights: This study is a comparison of commonly used Injury Metrics for evaluation of Traumatic Brain Injury. The study includes both an empirical comparison and a mathematical comparison of formal properties. This study is intended as a guideline to obtain new suitable Injury Metrics. Some new Injury Metrics are proposed and evaluated using data of pedestrian–vehicle collision. Abstract: Background and objective: Abrupt accelerations or decelerations can cause large strain in brain tissues and, consequently, different forms of Traumatic Brain Injury (TBI). In order to predict the effect of the accelerations on the soft tissues of the brain, many different injury metrics have been proposed (typically, an injury metric is a real valued functional of the accelerations). The objective of this article is to make a formal and empirical comparison, in order to identify general criteria for reasonable injury metrics, and propose a general guideline to avoid ill-proposed injury metrics. Methods: A medium-sized sample of vehicle–pedestrian collisions, from Post Mortem Human Subject (PMHS) tests, is analyzed. A statistical study has been conducted in order to determine the discriminant power of the usual metrics. We use Principal Component Analysis to reduce dimensionality and to check consistency among the different metrics. In addition, this article compares the mathematical properties of some of these functionals, trying to identify the desirable properties that any of those functionals needs to fulfill in order to be useful for optimization. Results: We have found a pair-wise consistency of all the currently used metrics (any two injury metrics are always positively related). In addition, we observed that two independent principal factors explain about 72.5% of the observed variance among all collision tests. This is remarkable because it indicates that despite high number of different injury metrics, a reduced number of variables can explain the results of all these metrics. With regard to the formal properties, we found that essentially all injury mechanisms can be accounted by means of scalable, differentiable and convex functionals (we propose to call minimization suitable injury metric any metric having these three formal properties). In addition three useful functionals, usable as injury metrics, are identified on the basis of the empirical comparisons. Conclusions: The commonly used metrics are highly consistent, but also highly redundant. Formal minimal conditions of a reasonable injury metric has been identified. Future proposals of injury metrics can benefit from the results of this study.